2019
DOI: 10.1111/jocn.14900
|View full text |Cite
|
Sign up to set email alerts
|

Discussing sexuality in health care: A systematic review

Abstract: Aims and objectives: Using the PRISMA guidelines, a systematic literature review was conducted to explore current and relevant evidence regarding factors that influence nurses' provision of sexual healthcare education to patients. Background: The World Health Organization and Healthy People 2020 emphasise the importance of sexual health care. Although the nursing profession has the ability to develop a competent level of sexuality education, sexual health care is often ignored in nursing care and education. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(158 citation statements)
references
References 17 publications
9
117
0
12
Order By: Relevance
“…For example, more often than physicians, the nurses in this study felt safer discussing sexual matters with patients, reported more sufficient knowledge to address questions, and believed they can effectively manage issues with either men or women. A systematic review of sexuality in health care determined sexual health care is not viewed by physicians as a medical problem (Fennell & Grant, 2019). Similarly, in addressing sexual health, Klaeson et al (2017) (Ha & Longnecker, 2010;Patel et al, 2019), including a lack of instruction for psychosocial concerns such as sexual health (Dennis & Elstein, 1980;Wagner, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, more often than physicians, the nurses in this study felt safer discussing sexual matters with patients, reported more sufficient knowledge to address questions, and believed they can effectively manage issues with either men or women. A systematic review of sexuality in health care determined sexual health care is not viewed by physicians as a medical problem (Fennell & Grant, 2019). Similarly, in addressing sexual health, Klaeson et al (2017) (Ha & Longnecker, 2010;Patel et al, 2019), including a lack of instruction for psychosocial concerns such as sexual health (Dennis & Elstein, 1980;Wagner, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also reported 65% of the adolescents received consultation or content related to sexual health during their visit, but the mean time was 36 s. Other studies have similarly reported sexual health conversations during primary care visits are low frequency with minimal depth (Donaldson et al., 2013; Klein & Wilson, 2002). Although sexual health is a historically important area for evidence‐based practice (Reynolds & Magnan, 2005), sexual health is often neglected by nurses and physicians (East & Hutchinson, 2013; Fennell & Grant, 2019; Tsimtsiou et al., 2006). Initiating sexual health discussions with patients has been described as opening a “can of worms” by Gott et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual health care and rehabilitation is an important but often neglected field in health and welfare practice, which may lead to decreased quality of life (Fennell & Grant, 2019;Haesler et al, 2016;Wang et al, 2018). Health care professionals often describe being insufficiently educated and feeling insecure when addressing sexual health in clinical practice (Fennell & Grant, 2019;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual health care and rehabilitation is an important but often neglected field in health and welfare practice, which may lead to decreased quality of life (Fennell & Grant, 2019;Haesler et al, 2016;Wang et al, 2018). Health care professionals often describe being insufficiently educated and feeling insecure when addressing sexual health in clinical practice (Fennell & Grant, 2019;Wang et al, 2018). In this article, we present how the International Classification of Functioning, Disability and Health (ICF) and the International Classification of Health Interventions (ICHI) can be used together in the health care process as well as in structured documentation in a health information system such as the electronic health record (EHR) to promote sexual health and related care.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual health care is often overlooked in nursing (26). This seems to be true in Iranian society because, in the Iranian culture, sexual issues have long been known as taboos (27).…”
Section: Introductionmentioning
confidence: 99%